The effect of intravenous iron on postoperative transfusion requirements in hip fracture patients: study protocol for a randomized controlled trial - Rowlands, Martin; Forward, Daren P.; Sahota, Opinder; Moppett, Iain K. (BioMed Central, 2013)
Background Anaemia following hip fracture is common. Approximately 30 to 45% of patients have haemoglobin concentrations below population norms on admission, and around 10% are severely anaemic. Anaemia on admission, and in the postoperative period, is associated with poor outcomes with regard to mobility, postoperative mortality and readmission. There is currently no clear consensus on the optimal method of managing perioperative anaemia in this group of frail patients with frequent comorbidity. Liberal red cell transfusion in the postoperative period does not appear to improve outcome, whereas tranexamic acid appears to reduce transfusion rate at the expense of increased cardiovascular morbidity. There are encouraging results from one centre with the use of agents to stimulate red cell production, including intravenous iron and erythropoietin. UK practice differs significantly from these patients and these studies, and it is not clear whether these promising results will translate to the UK population.